2001
DOI: 10.1002/hyp.234
|View full text |Cite
|
Sign up to set email alerts
|

The role of subsurface runoff through bedrock on storm flow generation

Abstract: Abstract:The influence of bedrock subsurface flow on storm runoff generation was investigated in Japan in two regions in Japan underlain by three bedrock types. One region, with approximately 2500 m of relief, is located in the Japan Alps, central Japan (In a region), where six small forest-covered watersheds underlain by granite and Mesozoic shale were studied. Two of these watersheds were instrumented to monitor stream discharge and the other four are springs occurring at the bedrock exposure. The other stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
121
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(134 citation statements)
references
References 24 publications
6
121
2
1
Order By: Relevance
“…Finally, we could not detect any dye staining at the soil-bedrock interface during our experiments. These findings are in contrast to many hillslope hydrology studies, where the soil-bedrock interface is described as a prominent lateral drainage feature (Onda et al, 2001;Tani, 1997;Uchida et al, 2002Uchida et al, , 2005.…”
Section: Runoff Formation and Shallow Landslidescontrasting
confidence: 99%
See 1 more Smart Citation
“…Finally, we could not detect any dye staining at the soil-bedrock interface during our experiments. These findings are in contrast to many hillslope hydrology studies, where the soil-bedrock interface is described as a prominent lateral drainage feature (Onda et al, 2001;Tani, 1997;Uchida et al, 2002Uchida et al, , 2005.…”
Section: Runoff Formation and Shallow Landslidescontrasting
confidence: 99%
“…Accordingly, SSF can develop along (1) soil pipes in the unsaturated zone (Mosley, 1979;Zuidema, 1985), (2) soil pipes in the saturated zone due to transient groundwater rise (Uchida et al, , 2005, (3) along preferential flow structures in the soil matrix in the saturated zone (Rohde, 1987;Sklash et al, 1986), or at (4) the soil-bedrock interface (Brammer and McDonnell, 1996; Tromp-van Meerveld 876 P. Schneider et al: Experimental identification of hydrological processes at a hillslope prone to slide . Other studies highlight the important role of the underlying bedrock, which can significantly contribute to runoff formation in steep terrain (Haught and Tromp-van Meerveld, 2011;Onda et al, 2001;Uchida et al, 2002Uchida et al, , 2005. Accordingly, it is important to understand to which extent the bedrock is connected to soil structures and the soil matrix, especially for predicting pore water pressure development in slopes, e.g., for predicting shallow landslides (Tromp-van Meerveld and Weiler, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many catchments reportedly showing double-peak hydrographs are headwater catchments with predominantly steep slopes and shallow soils, and in many cases with periglacial slope deposits (Burt and Butcher, 1985;Onda et al, 2001;Graeff et al, 2009;Birkinshaw and Webb, 2010;Fenicia et al, 2014;Wrede et al, 2015;MartĂ­nez-Carreras et al, 2016). Such systems are characterized by pronounced subsurface structures and therefore are prone to heterogeneous flow patterns and preferential flow at the plot and hillslope scale.…”
Section: Synthesis: Functioning Of the Investigated Hillslopementioning
confidence: 99%
“…This hypothesis is backed by a study comparing catchments of different geology (Onda et al, 2001), where the prolonged response of double-peak hydrographs was identified as an indicator of deeply percolating subsurface flow through bedrock fissures. This theory might also apply to the catchment investigated here, with its fractured schist bedrock (Kavetski et al, 2011).…”
Section: Synthesis: Functioning Of the Investigated Hillslopementioning
confidence: 99%
“…Fenicia et al, 2010). Groundwater dynamics and subsurface flow pathways are a key control on runoff generation and flow dynamics in a variety of different catchments (Onda et al, 2001;Soulsby et al, 2007), with strong evidence coming from hydrochemical analysis of streamwater. The hydrology of the riparian zone may be particularly sensitive to groundwater connections (Vidon and Hill, 2004).…”
Section: Introductionmentioning
confidence: 99%